The Effect of Motivation, Job Satisfaction, Organizational Culture and Work Environment on Organizational Commitment to Employees: Pengaruh Motivasi, Kepuasan Kerja, Budaya Organisasi dan Lingkungan Kerja Terhadap Komitmen Organisasi Pada Karyawan - Heriyanto, Muhammad Ferdiawan; Rizal, Asat (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of motivation, job satisfaction, organizational culture, and work environment on organizational commitment to employees of PT. Jasa Marga Pandaan-Malang. This study uses quantitative methods. The type of research used is descriptive research. The population in this study were all employees of PT. Jasa Marga Pandaan-Malang, which has 96 employees. Sampling using the "saturated sample" technique resulted in 96 respondents. Data collection techniques used are questionnaires and interviews. The analytical technique used in this research is multiple linear regression using SPSS version 18 program. The results of this study indicate that the simultaneous test of motivation, job satisfaction, organizational culture, and work environment variables have an influence on organizational commitment of PT. Jasa Marga Pandaan-Malang. The variable that has the most significant effect on organizational commitment is the work environment variable. Keywords – Motivation; Job satisfaction; Organizational culture; Work environment; Organizational Commitment